2017
DOI: 10.1371/journal.pone.0170217
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Community Health Resources on Effectiveness and Sustainability of Community and Lay Health Worker Programs in Lower-Income Countries: A Systematic Review

Abstract: BackgroundDespite the availability of practical knowledge and effective interventions required to reduce priority health problems in low-income countries, poor and vulnerable populations are often not reached. One possible solution to this problem is the use of Community or Lay Health Workers (CLHWs). So far, however, the development of sustainability in CLHW programs has failed and high attrition rates continue to pose a challenge. We propose that the roles and interests which support community health work sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 53 publications
0
48
2
Order By: Relevance
“…Out of the few studies we found that used randomized controlled experiments to test recruitment and retention strategies, almost all had high or unclear risk of bias. Additionally, strategies previously touted as important to increasing participation, such as increasing trust (Corbie-Smith, Thomas, Williams, & Moody-Ayers, 1999;Ford, Havstad, & Davis, 2004;Fracasso et al, 2013;Gwadz et al, 2014) , did not differentiate between "winning" and "ineffective" interventions while research process-related strategies (e.g. systematic contact plan) did.…”
Section: Discussionmentioning
confidence: 92%
“…Out of the few studies we found that used randomized controlled experiments to test recruitment and retention strategies, almost all had high or unclear risk of bias. Additionally, strategies previously touted as important to increasing participation, such as increasing trust (Corbie-Smith, Thomas, Williams, & Moody-Ayers, 1999;Ford, Havstad, & Davis, 2004;Fracasso et al, 2013;Gwadz et al, 2014) , did not differentiate between "winning" and "ineffective" interventions while research process-related strategies (e.g. systematic contact plan) did.…”
Section: Discussionmentioning
confidence: 92%
“…CHW programs have been implemented in many different nations around the world with varying degrees of success (2). A number of characteristics of the Rwandan CHW program arose in this research that have been considered integral to successful CHW programs in the literature: CHWs live in and are selected by their neighbors for their role, they have frequent interactions with and are well-respected by members of their communities -which serves as the most important method of supervision, and the links between CHWs and the formal health sector is strong (2,3,6,26). The success of the Rwandan CHW program could ultimately be due to government support and respect of CHWs that sets up the pathways associated with successful CHW programs (22,26).…”
Section: Discussionmentioning
confidence: 99%
“…One route to increasing access to primary care for all persons, particularly for populations hardest to reach, is via community health worker (CHW) programs (2). CHW programs provide primary comprehensive healthcare in the community (3), and extant research shows that the most effective programs have CHWs who are elected members of the communities that they serve (2). Despite some challenges identi ed in sustaining CHW programs, research thus far suggests that CHWs are a worthy investment for public health (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposures were another important source of ambient air pollution exposure. Activities included limestone processing in Zambia (Bwalya et al, 2011), exposure to desert dust in West Africa [reviewed by de Longueville et al (2013)], traffic exhaust (DeMarini, 2013), dust and fumes in artisanal mining (Ekosse, 2011), city transit-related air pollution Ekpenyong et al, 2012), stone quarrying industry exposures including deposition of inhaled aerosol particles at an industrial site in Egypt (Furi et al, 2017), sulfur dioxide (SO2) emissions from platinum group metal (PGM) smelting in Zimbabwe (Gwimbi, 2017), and charcoal processing activities in Namibia, including exposure to charcoal dust (Hamatui et al, 2016). DNA adducts to measure air pollution exposure among urban and suburban residents was also implemented in some studies (Ayi-Fanou et al, 2011).…”
Section: Exposures Measuredmentioning
confidence: 99%
“…Developments in pharmacogenomics (Warnich et al, 2011) and the human microbiome (Adebamowo et al, 2017) are also underway, and many studies incorporate information about HIV, malaria, tuberculosis, and other common infections in Africa. The H3Africa consortium also promotes opportunities for training in bioinformatics (Adoga et al, 2014;Oluwagbemi et al, 2014;Mulder et al, 2016), supports three biorepositories on the African continent, and facilitates policy and ethical recommendations (Consortium et al, 2014;Barchi and Little, 2016;Munung et al, 2016;de Vries and Pool, 2017).…”
Section: Introductionmentioning
confidence: 99%